Lateral window technique: a focus review - Correia, Francisco (2021)
The posterior alveolar bone region of the maxilla has, in more than 40% of the cases, a height inferior to 4 mm, thus making rehabilitation with implants a clinical challenge. This focus literature review was carried out through an exhaustive literature search in PubMed, ScienceDirect, LILACS, Web of Science, Scielo and Cochrane Library. The aim was to illustrate and analyse various factors that should be accounted for while applying the maxillary sinus elevation technique. The lateral osteotomy technique is carefully described including its indications, complications, contraindications, as well as, different factors to take into account, such as the use of electric piezo, graft materials, membranes and the expected success rates.